(untitled) (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2023)
The present volume Immersions and Dives: From the Environment to Virtual Reality of the journal AN-ICON: Studies in Environmental Images is divided into two issues, each one dedicated to a specific thematic analysis, originated by the same conceptual core. The volume reflects on the concept of immersivity, which has become increasingly prominent in many different fields, including contemporary art. The constant reference to immersive experience is redefining the boundaries of artistic practice and fruition, highlighting the complex relationships between art, environments, and human perception.